Is heterogeneous expression of HLA-dr antigens and CEA along with DNA-profile variations evidence of phenotypic instability and clonal proliferation in human large bowel carcinomas? - Rognum, T. O. (Nature Publishing Group, 1983)
Epithelial expression of HLA-DR determinants and CEA was studied by immunofluorescence in tissue sections from 33 large bowel carcinomas of different histological grade and clinico-pathological stage; flow cytometric DNA measurements were performed in 31 of the tumours. Well-differentiated carcinomas showed a strikingly patchy staining, particularly for HLA-DR and all except one had a near-diploid DNA content. The latter feature might reflect cancer development at an early stage where no distinctly aneuploid DNA clone had as yet become a predominant subline. With decreasing degree of differentiation, the epithelial antigen expression became more homogeneous for individual tumours and the proportion of distinctly aneuploid DNA profiles increased. In the poorly differentiated group of carcinomas, epithelial staining was quite uniform, both for HLA-DR determinants and for CEA, and those tumours studied for DNA content were of the aneuploid variety. These observations are in agreement with the clonal proliferation theory of tumour development proposed by Nowell in 1976. IMAGES: